2021
DOI: 10.1021/jacs.1c10756
|View full text |Cite
|
Sign up to set email alerts
|

Manganese(I)-Catalyzed H–P Bond Activation via Metal–Ligand Cooperation

Abstract: Here we report that chiral Mn­(I) complexes are capable of H–P bond activation. This activation mode enables a general method for the hydrophosphination of internal and terminal α,β-unsaturated nitriles. Metal−ligand cooperation, a strategy previously not considered for catalytic H–P bond activation, is at the base of the mechanistic action of the Mn­(I)-based catalyst. Our computational studies support a stepwise mechanism for the hydrophosphination and provide insight into the origin of the enantioselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 44 publications
0
59
0
Order By: Relevance
“…A recent advance was made by Ge and Harutyunyan employing a chiral manganese(I) catalyst for the asymmetric hydrophosphination of ,-unsaturated nitriles. [150] Interestingly, this is a rare example of metal-ligand cooperation in hydrophospination catalysis where both the metal and ligand participated in P-H bond activation (Scheme 74). As the second most abundant transition metal, the use of manganese also represents both progress in asymmetric hydrophosphination and sustainability in catalyst design.…”
Section: Scheme 67mentioning
confidence: 99%
“…A recent advance was made by Ge and Harutyunyan employing a chiral manganese(I) catalyst for the asymmetric hydrophosphination of ,-unsaturated nitriles. [150] Interestingly, this is a rare example of metal-ligand cooperation in hydrophospination catalysis where both the metal and ligand participated in P-H bond activation (Scheme 74). As the second most abundant transition metal, the use of manganese also represents both progress in asymmetric hydrophosphination and sustainability in catalyst design.…”
Section: Scheme 67mentioning
confidence: 99%
“…11–13 Next to these reports, we have recently demonstrated that such complexes are capable of catalytic H–P bond activation of diarylphosphines. 8 Based on these findings we hypothesised that Mn( i )-complexes should be able to bring the phosphine oxide and the phosphine reagents into closer proximity thus allowing the hydrophosphination reaction to take place directly with α,β-unsaturated phosphine oxides. This approach would avoid the additional synthetic steps and purifications procedures necessitated by the installation and removal of the sulphur atom that are intrinsic to the method utilising phosphine sulphides.…”
mentioning
confidence: 97%
“…From a mechanistic point of view, we wondered whether our base activated Mn-catalyst I is involved in the activation of the phosphine reagent 2a via ligand–metal cooperation, as proposed in our previous work on α,β-unsaturated nitriles, 8 or whether it also plays a role in the activation of the phosphine oxide substrate 1. Preliminary NMR spectroscopic studies did not reveal any interaction between I and 1 (see ESI†) leading us to hypothesise that the current transformation might follow a mechanistic path that primarily involves phosphine activation, as depicted in Scheme 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent advance was made by Ge and Harutyunyan employing a chiral manganese(I) catalyst for the asymmetric hydrophosphination of ,-unsaturated nitriles. [147] Interestingly, this is a rare example of metal-ligand cooperation in hydrophospination catalysis where both the metal and ligand participated in P-H bond activation (Scheme 69). As the second most abundant transition metal, the use of manganese also represents both progress in asymmetric hydrophosphination and in sustainability in catalyst design.…”
mentioning
confidence: 99%